Analyzing Foreign Market Entry Strategies: Extending the Internalization Approach - Buckley, Peter J.; Casson, Mark C. (Journal of International Business Studies, 1998)
A new fully integrated analysis of the foreign market entry decision is presented, encompassing the choice between exporting, licensing, joint venturing and wholly owned foreign investment. The choice between acquisition and greenfield investment is examined, and so too are options based on subcontracting and franchising. The model extends the insights of internalization theory, and draws on concepts from the economics of industrial organization. A special feature of the model is the distinction between investment in production facilities and investment in distribution facilities - an important practical distinction that has been overlooked in much of the international business literature. The strength of competition from indigenous rivals is emphasized as a determinant of entry strategy into both production and distribution.